Aerobiological data as an indicator for invasive plants monitoring - Guillermo Guada; Fernando Veiga-López; María Fernández-González; J. José Uzal-Dapena; José Ángel Cid-Fernández; F. Javier Rodríguez-Rajo (Ecological Indicators)
The relationship between airborne pollen of the invasive species Acacia dealbata Link, climate factors, and its ground expansion is studied using aerobiological data and aerial photography to test if pollen data can be used as a tool to detect changes in the surface area of invasive species.Airborne pollen monitoring was performed over a 31 years period (1994–2024). Additionally, eight years within this interval were selected for Acacia area measurement with high-resolution aerial imagery, based on the availability of photographs.Aerial pollen recorded correlated significantly with maximum temperatures during the pre-peak period, stabilizing the correlation in the time series after 23 years. Additionally, the pollen integral showed an increasing trend that was not climate dependent. Mapped Acacia areas expanded from 200.2 ha in 1994 to 273.7 ha in 2024, a 36.7 % increase reflected in the increase of pollen levels, reaching a 2.3-fold rise.Acacia stabilizes and even reduces its surface during the last years of study. The interaction of pollen recorded in pre-peak period and maximum temperature explains 77 % of the invasion of Acacia surface variation, with an estimated area error of 16.51 ha. It is concluded that Acacia pollen serves as a new indicator to monitor Acacia surface and reconstruct its cover in the absence of high-resolution aerial images. Monitoring pollen concentrations in the atmosphere constitutes a useful tool for the management of invasive species.